Direct measurement of punch force during six professional boxing matches - Pierce, J. D.; Reinbold, K. A.; Lyngard, B. C.; Goldman, R. J.; Pastore, C. M. (Journal of Quantitative Analysis in Sports, 2006)
Despite considerable research into boxing, surprisingly little is known concerning the fundamental physics of forces delivered in a boxing match. Most previous punch force estimates have been obtained from laboratory studies in which an experienced boxer struck an inanimate object. This paper presents the first direct measurement of punch force in professional boxing matches. Measurements were made using a proprietary system that records the force associated with punch impact. Twelve boxers wore boxing gloves incorporating the bestshot System TM in six professional boxing matches across five different weight classes. The force of each delivered punch was measured across all rounds of all bouts. Mean punch forces delivered ranged from 866.6 N (Super Middleweight) to 1149.2 N (Light Middleweight) across the fights and was not significantly correlated with boxer´s weight. In each of the three bouts where the outcome was determined by judges? decision, the boxer delivering the greater cumulative force and the greater number of punches won unanimously. These measurements, the first direct measurement of punch force in professional boxing matches, are considerably less than those found in laboratory demonstrations, and likely reflect the dynamic nature of the ring. The ability to measure punch force directly may be beneficial in training, judging, and monitoring the health of boxers during competitive matches.